1998
DOI: 10.1029/98ja02291
|View full text |Cite
|
Sign up to set email alerts
|

Inner magnetospheric superthermal electron transport: Photoelectron and plasma sheet electron sources

Abstract: On the nightside, the inner plasmasphere is usually unheated by superthermal electrons. A feature of these combined spectra is that the distribution often has upward slopes with energy, particularly at the crossover from PE to PSE dominance, indicating that instabilities are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…While the heating rates given by Khazanov et al [1998Khazanov et al [ , 2000 are also at solar maximum, the geomagnetic activity was considerably different (that is, less intense), and thus it is not surprising that this heat flux is larger. There is strong local time asymmetry in the heating, and the peak is located toward lower latitudes near dusk.…”
Section: Heat Input Into the Thermal Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the heating rates given by Khazanov et al [1998Khazanov et al [ , 2000 are also at solar maximum, the geomagnetic activity was considerably different (that is, less intense), and thus it is not surprising that this heat flux is larger. There is strong local time asymmetry in the heating, and the peak is located toward lower latitudes near dusk.…”
Section: Heat Input Into the Thermal Electronsmentioning
confidence: 99%
“…Plate 1 [Khazanov et al, 1998. While the heating rates given by Khazanov et al [1998Khazanov et al [ , 2000 are also at solar maximum, the geomagnetic activity was considerably different (that is, less intense), and thus it is not surprising that this heat flux is larger.…”
Section: Heat Input Into the Thermal Electronsmentioning
confidence: 99%
“…Coulomb collisions with ring current ions (Kozyra et al, 1987) and different kinds of wave-particle interactions (Khazanov et al, 1996) were considered to explain this increase in temperature. Khazanov and Liemohn (2002) and Khazanov et al (1998) also analyzed plasmaspheric heating from atmospheric photoelectrons and showed more heating in the outer plasmasphere than in the deep inner plasmasphere on the nightside.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, during the main phase the overlap of these two regions is minimal, possibly causing the lack of heating in the nightside plasmasphere at this time period. Khazanov et al (1998) showed that at least at L43 photoelectrons cannot heat the nightside during storm times. But as the observed temperatures during the storm main phase are lower than the temperatures before the storm, it is likely that some cooling process is also involved.…”
Section: Discussionmentioning
confidence: 98%
“…These precipitating electrons are presumably of solar wind origin, but they could also be photoelectrons, trapped during the day and dumped into the ionosphere sometime during the night. At Earth, trapped photoelectrons slowly precipitate throughout the night, contributing to the thermal balance of the ionospheric F layer (e.g., Nagy and Banks, 1970;Swartz et al, 1975;Khazanov et al, 1998Khazanov et al, , 2000. The MEX observations of high-altitude photoelectrons could be related to trapping within mini-magnetospheres.…”
Section: Introductionmentioning
confidence: 94%